Colorectal cancer in pregnancy mimicking tuberculosis - Wadhwa, Leena; Nain, Shilpi; Kataria, Sonia; Jindal, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Colorectal cancer in pregnancy is extremely rare and presentation may mimic symptoms of pregnancy or abdominal tuberculosis delaying diagnosis. We hereby report a case presenting to us in late pregnancy misdiagnosed as a case of abdominal tuberculosis.